Comportamiento morfoagronómico y productivo de genotipos de piñon (Jatropha curcas L.), en el valle del río Carrizal - Intriago Martínez, Roberta Estefanía (2023)
The pine nut is a shrub or tree that can reach 6 to 8 meters in height and a longevity of more than 50 years, in addition to being used as a living stock in stables or paddocks. The objective of the research was to evaluate the morphoagronomic and productive behavior of foreign pinyon genotypes in the Carrizal river valley. The experiment was carried out in an established area of the polytechnic campus located in the El Limon site belonging to the Bolivar Canton, Manabí province. The experiment was established under a randomized complete block design (DBCA) with six treatments, four repetitions, a total of 24 experimental units. The experimental unit consisted of plots of 24 plants, where the data was recorded in the 8 central plants. The morphoagronomic behavior of four introduced hybrids vs. two local varieties of pinyon under conditions of the Carrizal river valley was studied. It is concluded that the hybrid JAT-001164 stood out with better attributes in terms of behavior and yield and could be an alternative to improve the productive potential in several locations in the Carrizal river valley.